Fully reconfigurable photonic microwave transversal filter based on digital micromirror device and continuous supercontinuum source - Lee, Ju Han; Chang, You Min; Han, Young-Geun; Lee, Sang Bae; Chung, Hae Yang (OPTICAL SOC AMER, 2007)
The combined use of a programmable, digital micromirror device (DMD) and an ultrabroadband, cw, incoherent supercontinuum (SC) source is experimentally demonstrated to fully explore various aspects on the reconfiguration of a microwave filter transfer function by creating a range of multiwavelength optical filter shapes. Owing to both the unique characteristic of the DMD that an arbitrary optical filter shape can be readily produced and the ultrabroad bandwidth of the cw SC source that is 3 times larger than that of Er-amplified spontaneous emission, a multiwavelength optical beam pattern can be generated with a large number of wavelength filter taps apodized by an arbitrary amplitude window. Therefore various types of high-quality microwave filter can be readily achieved through the spectrum slicing-based photonic microwave transversal filter scheme. The experimental demonstration is performed in three aspects: the tuning of a filter resonance bandwidth at a fixed resonance frequency, filter resonance frequency tuning at a fixed resonance frequency, and flexible microwave filter shape reconstruction. (c) 2007 Optical Society of America.
Keywords: LIGHT; FIBER